Evaluating Destination Management Performance in Emerging Coastal Tourism: A Case Study of Al Fath Stira Paradise Beach, Indonesia - Darwis; Firdhanur Hedar; Sudarmi; I Nyoman Siryayasa; Masri Ridwan (Institut Pariwisata dan Bisnis Internasional, 2026)
This study aims to evaluate destination management practices at Al Fath Stira Paradise Beach, an emerging coastal tourism destination in Pinrang Regency, Indonesia. A descriptive quantitative approach was employed, involving 105 respondents consisting of visitors, tourism business actors, and destination managers. Data were collected through structured questionnaires, field observations, and supporting documents, and analyzed using descriptive statistical techniques. The findings reveal that overall destination management performance is categorized as good, particularly in promotion (85.7%), cleanliness (up to 83.8%), and service quality, including staff friendliness (82.9%) and professionalism (81.0%). However, several key weaknesses remain, particularly in attraction innovation (62.9%), stakeholder communication (65.7%), and consistency of facility maintenance. The planning dimension demonstrates a relatively strong foundation, especially in data-based decision-making (83.8%), but lacks optimal stakeholder involvement. In addition, the results indicate that while social media promotion is effective, collaboration with external partners is still limited. This study contributes both theoretically and practically by providing empirical evidence on the implementation of destination management in a local coastal context. The findings highlight the need for more structured planning, stronger stakeholder coordination, continuous attraction development, and integrated promotion strategies to enhance destination competitiveness and sustainability. The study offers practical recommendations for policymakers and destination managers to improve tourism management in emerging coastal destinations